Simplify 2ln(e^3) / [ln(1) - ln(e)]?

nuff said

4 Answers

Relevance
  • 1 decade ago
    Favorite Answer

    2 ln(e³) / (ln(1) - ln(e))

    = 6 / (0 - 1)

    = -6

    Answer: -6

  • 1 decade ago

    Move the 2 in 2ln(e^3) to inside the brackets to make ln (e ^ 6).

    Combine the two terms in ln 1 - ln e, which becomes ln (1/e)

    Because ln e = 1, and ln(e^6) can be expressed in 6(ln e), then the numerator = 6.

    The denominator can expressed as ln (e^ -1), which equals -ln e, which equals -1.

    Therefore, 6/ -1 = -6, and thats ur answer.

    Hope it helps

  • 1 decade ago

    In e =1

    In e^3 =3

    In (1) = 0

    In (-e) = -In (e) = -1

    So 2In e^3 /(In(1)-In(e)) = 6/(0-1) = -6

  • 1 decade ago

    2(3)/[ln1-1]

    6/((ln1)-1)

Still have questions? Get your answers by asking now.